PREFERENSI MUSLIM TERHADAP PEMBELIAN PRODUK MAKANAN IMPOR BERSERTIFIKASI HALAL DI KOTA MALANG - Al Muqaffi, Dzakka (Islamic Economics and finance in Focus, 2022)
Being the country with the most Moslem population in the world, Indonesia has a variety of halal foods that can be addressed to its consumers. This is a distinct advantage for both local and foreign economic actors. With a large population, of course, foreign businessmen are also interested in exporting their products to Indonesia, including food products. With the development of technology, it can affect a person's lifestyle where everyone can access social media easily. With the existence of social media, sellers will find it easier to advertise their products so that it can lead to increased consumer demand. Imported food itself is being favored by many people today, although local food can also compete there. As a Moslem, of course, the halalness of a product is the main thing to look at before buying a product. In this case, the Moslem's is guaranteed by the 1945 Constitution. Therefore, the state is also responsible for and guarantees the halalness of products consumed by Moslems in Indonesia. This study aims to determine the factors that influence Moslem preferences for purchasing halal-certified imported food products in Malang City. The analysis used is descriptive statistical analysis with logistic analysis method. The results of this study indicate that there is a simultaneous significant effect between the independent variables on the dependent variable. Meanwhile, partially, only one independent variable has a significant effect on the dependent variable, namely the price variable.